Electroconvulsive therapy improves distal colonic motility via the subdiaphragmatic vagus nerve in depressive-like mice - Mengyao Dai; Yanzhang Li; Yanghua Tian (Scientific Reports)
Abstract Depression is a common mood disorder characterized by persistent sadness, loss of interest or pleasure, and a range of cognitive and physical symptoms such as gastrointestinal dysfunction that significantly impair daily functioning. Electroconvulsive Therapy (ECT) remains the treatment of choice and a critical last-resort intervention for patients with severe, treatment-resistant depression, particularly those at high risk of suicide. Evidence suggests that the gut-brain axis, a complex bidirectional communication network, plays a key role in the development of these multifaceted symptoms. This study explores the possibility that ECT may exert its therapeutic effects by modulating gastrointestinal function. In clinical investigation, a notable proportion of patients with major depressive disorder experienced significant alleviation of gastrointestinal symptoms, particularly constipation, following ECT. In preclinical research, Electroconvulsive Shock (ECS) is commonly applied to animal models as an experimental analogue to explore the mechanisms and efficacy of ECT. Complementary experiments in mice revealed that daily ECS not only reversed depressive-like behaviors but also restored colonic motility. This effect was closely associated with the normalization of neural activity in the hypothalamic paraventricular nucleus (PVN), a key brain region involved in autonomic nervous regulation. Importantly, these benefits were abolished by subdiaphragmatic vagotomy, underscoring the pivotal role of the vagus nerve in mediating gut-brain interactions. These findings offer insights into the neural pathways underpinning the gut-brain connection, highlighting the potential of ECT not only as a last line of defense against severe depression but also as a means to address associated gastrointestinal dysfunction.